The Application Of Course Review Horay to Increase Liveliness and Learning Outcomes - Anggraeny, Gita (Unversitas Negeri Malang, 2017)
Learning often makes the students feel bored and had less spirit to study because the teacher applied conventional learning model or speech. That model affected less student activity and lower learning outcome. Because of that case we need an interesting learning model which can make the students become more interested in the learning process. This learning model is Course Review Horay. This research was done in class XI IPS 5 Senior High School 1 Tumpang. The amount of the student in this class is 20 student that consists of 14 boys and 6 girls. The data about the implementation of learning model Course Model Horay obtained through an instrument called teacher activity observation sheet. Based on data that had been obtained through student activity and their learning outcome in Class XI IPS 5. It can be shown with the successfulness of this action research in implementing learning model Course Model Horay in the First cycle reaches 65% with good category (B) then there’s an improvement in the second cycle, that ‘s about 82% with very good category (A). The improvement of learning outcome in the first cycle, that’s about 78% change to 87% in the second cycle, or increased by 9 %. While the increased activity on the first cycle of 72 % and increases significantly every cycle for the second 79 %. Based on the outcome of this research, can be concluded that the implementation of learning model Course Review Horay can increase liveliness and study results students, and suggested for teachers especially teachers economic to apply learning model so that the liveliness and study result students can increase. Keywords: Course Review Horay, Increase Liveliness, Learning Outcomes